Effects of hypothyroidism on the structure and mechanical properties of bone in the ovine fetus. - Lanham, SA; Fowden, A; Roberts, C; Cooper, C; Oreffo, R; Forhead, A (2011)
Thyroid hormones are important for normal bone growth and development in postnatal life. However, little is known about the role of thyroid hormones in the control of bone development in the fetus. Using computed tomography and mechanical testing, the structure and strength of metatarsal bones were measured in sheep fetuses in which thyroid hormone levels were altered by thyroidectomy or adrenalectomy. In intact fetuses, plasma concentrations of total calcium and the degradation products of C-terminal telopeptides of type I collagen increased between 100 and 144 days of gestation (term 145±2 days), in association with various indices of bone growth and development. Thyroid hormone deficiency induced by thyroidectomy at 105-110 days of gestation caused growth retardation of the fetus and significant changes in metatarsal bone structure and strength when analyzed at both 130 and 144 days of gestation. In hypothyroid fetuses, trabecular bone was stronger with thicker, more closely spaced trabeculae, despite lower bone mineral density. Plasma osteocalcin was reduced by fetal thyroidectomy. Removal of the fetal adrenal gland at 115-120 days of gestation, and prevention of the prepartum rises in cortisol and triiodothyronine, had no effect on bodyweight, limb lengths, metatarsal bone structure or strength, or circulating markers of bone metabolism in the fetuses studied near term. This study demonstrates that hypothyroidism in utero has significant effects on the structure and strength of bone, with different consequences for cortical and trabecular bone.